Whole-Body Cryotherapy Decreases the Levels of Inflammatory, Oxidative Stress, and Atherosclerosis Plaque Markers in Male Patients with Active-Phase Ankylosing Spondylitis in the Absence of Classical Cardiovascular Risk Factors. (1st February 2018) - Stanek, Agata; Cholewka, Armand; Wielkoszyński, Tomasz; Romuk, Ewa; Sieroń, Aleksander
Abstract : Objective . The aim of the study was to estimate the impact of whole-body cryotherapy (WBC) on cardiovascular risk factors in patients with ankylosing spondylitis (AS). Material and Methods . We investigated the effect of WBC with subsequent kinesiotherapy on markers of inflammation, oxidative stress, lipid profile, and atherosclerosis plaque in male AS patients (WBC group). To assess the disease activity, the BASDAI and BASFI were also calculated. The results from the WBC group were compared with results from the kinesiotherapy (KT) group. Results . The results showed that in the WBC group, the plasma hsCRP level decreased without change to the IL-6 level. The ICAM-1 level showed a decreasing tendency. The CER concentration, as well as the BASDAI and BASFI, decreased in both groups, but the index changes of disease activity were higher in the WBC than KT patients. Additionally, in the WBC group, we observed a decrease in oxidative stress markers, changes in the activity of some antioxidant enzymes and nonenzymatic antioxidant parameters. In both groups, the total cholesterol and LDL cholesterol, triglycerides, sCD40L, PAPP-A, and PLGF levels decreased, but the parameter changes were higher in the WBC group. Conclusion . WBC appears to be a useful method of atherosclerosis prevention in AS patients.